Pengembangan Lembar Kerja Siswa (Lks) Berbasis Saintifik pada Mata Pelajaran Matematika SD - Restu Ayu Putri; Novianti Mandasari; Andriana Sofiarini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to develop teaching material products in the form of scientific-based Student Worksheets (LKS) in the fourth grade Mathematics subject of SD Negeri Napallicin which are valid and practical to use in the learning process. The research method is R&D (Research and Development), using the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). Data collection techniques used are interviews and questionnaires. The data analysis technique used a Likert scale and a Guttman scale. The results of the study based on the analysis of the linguist's assessment showed 0.80 and the validation results of media experts were 0.91 and the results of material validation were 0.79. Overall, the results of the analysis and calculation of the questionnaire scores from the expert team, scientific-based LKS are in the high category with a percentage of 0.83. While the results of the practicality test of teachers are classified as very practical and the results of the one to one trial are classified as very practical and the results of the small group trial are classified as very practical. The overall results of the practicality test are in the very practical category with a percentage of 88.5% so that it can be concluded that scientific-based worksheets in Mathematics are valid and practical to use. Keywords: Development, Student Worksheet, Scientific, Mathematics.